2015
DOI: 10.1080/09540121.2015.1035861
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms among patients infected with human immunodeficiency virus in South Korea

Abstract: Patients infected with human immunodeficiency virus (HIV) may develop mental health problems such as anxiety and depression, which negatively impact of disease progression. We investigated factors associated with the prevalence of anxiety and depression symptoms among HIV-infected patients in Korea. A total of 840 HIV-infected patients who participated in the Korea HIV/AIDS Cohort Study from 2006 to 2012 were evaluated. Socio-demographic, epidemiologic, and clinical variables were obtained through standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…76 More recent studies have revealed that anxiety and depressive symptoms occur signi ficantly more frequently in PLWHA compared to the general population. 54 The etiological factors to both anxiety and HIV include alcohol and substance abuse, males having sex with males, or males having a bisexual relationship. 77 Increased anxiety symptoms in PLWHA were associated with being a former smoker, HIV infection detected within the past year, persistent symptoms presenting for .7 days in the past 6 months, 54 pain, concurrent substance use disorder, minimal family support, and the spouse having AIDS.…”
Section: Depression and Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…76 More recent studies have revealed that anxiety and depressive symptoms occur signi ficantly more frequently in PLWHA compared to the general population. 54 The etiological factors to both anxiety and HIV include alcohol and substance abuse, males having sex with males, or males having a bisexual relationship. 77 Increased anxiety symptoms in PLWHA were associated with being a former smoker, HIV infection detected within the past year, persistent symptoms presenting for .7 days in the past 6 months, 54 pain, concurrent substance use disorder, minimal family support, and the spouse having AIDS.…”
Section: Depression and Hiv Infectionmentioning
confidence: 99%
“…54 The etiological factors to both anxiety and HIV include alcohol and substance abuse, males having sex with males, or males having a bisexual relationship. 77 Increased anxiety symptoms in PLWHA were associated with being a former smoker, HIV infection detected within the past year, persistent symptoms presenting for .7 days in the past 6 months, 54 pain, concurrent substance use disorder, minimal family support, and the spouse having AIDS. 78 In a study based in India, anxiety disorders were detected in 36% PLWHA, the majority of whom had GAD.…”
Section: Depression and Hiv Infectionmentioning
confidence: 99%
“…In chronic HIV infection, reported rates of clinically relevant depression range from 7% to 42%, with anxiety ranging from 13% to 53% [5, 6, 7, 8, 9, 10, 11]. In a study of recently infected individuals, some of whom had been infected for only a few weeks (i.e., acute HIV infection) over 20% reported suicidal ideation in the preceding month [12].…”
Section: Introductionmentioning
confidence: 99%
“…Initial diagnosis with HIV is associated with significant stress, as is the prospect of disclosure of diagnosis and having to live with HIV (Hult et al, 2012; Olley et al, 2005). While the general diagnosis and prevalence of anxiety and depression vary across cultures (Lewis-Fernandez et al, 2010), these symptoms have been widely reported in HIV-positive patient cohorts across the globe (Kee et al, 2015; Mutumba et al, 2015; Tesfaye and Bune, 2014). This cross-cultural prevalence raises the possibility that in addition to psychosocial stressors, a component of HIV infection may trigger anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%